Advanced developments in nonstoichiometric tungsten oxides for electrochromic applications. Issue 21 (1st October 2021) - Zeb, Shah; Sun, Guoxin; Nie, Yong; Xu, Huiyan; Cui, Yu; Jiang, Xuchuan
Abstract : This review summarizes the recent progress of WO3− x for switchable smart devices, focusing on the synthesis, film fabrication, and strategies to improve EC properties, followed by challenges and future development in multifunctional devices. Abstract : Nanoscale tungsten oxides (WO3 /W18 O49 ) are a hot research topic because of their impeccable performance in different fields, such as multi-step responses to one stimulus or selective response to a stimulus under controlled conditions, particularly electrochromic performance and energy saving applications in dynamic controllable smart windows. To satisfy different environments, the transparency and thermal insulation of windows are particularly tailored to reduce energy consumption, thereby decreasing cooling and heating costs. In this review, the nonstoichiometric tungsten oxides (WO3− x ) are presented in detail, summarized, and discussed, focusing on various methods for the synthesis of W18 O49 and WO3, such as chemical vapor deposition (CVD), physical vapor deposition (PVD), sol–gel, solvothermal, and hydrothermal methods, together with the synthetic strategies for the corresponding thin coatings. Then, the advanced strategies to improve the EC performance of nonstoichiometric W18 O49 nanostructures for multi-functionality EC smart windows are discussed. Furthermore, the fundamental mechanisms in coloration/bleaching related to oxygen vacancies, hybridization, elemental doping and surface decoration are explored and discussed in detail. Finally, the key challenges, future developments, and remarks to improve the variability of EC smart windows, such as energy harvesting and energy storing multifunction, coloration enhancement, stability, durability, and reducing toxicity are also highlighted accordingly.